Co-creating design for health in a city hospital: perceptions of value, opportunity and limitations from 'Designing Together' symposium. Issue 1 (2nd January 2019) - Cunningham, Helen; Reay, Stephen
Abstract: This research explores how co-creation and a design-led approach to the traditional notion of symposium brought together industry, academia and the voice of patients in a hospital-based environment. The symposium 'designing together' provided a primer to consider what opportunities and constraints might influence how design could thrive in a hospital environment. The qualitative survey based response, from 21 participants, was analyzed using a general inductive approach to uncover themes relating to the need for change versus resistance to change within the hospital, the need for a patient-centred approach balanced with the need to engage staff throughout design processes, and demonstrating the value of design balanced against financial constraints. Encouraging collaborative co-creation and insight from patients, staff and designers within a free public hospital event was a unique approach that may provide a useful template for designers, researchers and public health professionals in developing the future design in health collaborations.